Optimal Design and Analysis of Wide-Band Near-Infrared Hybrid Dielectric Gratings with High Transmission Efficiency - Ye Wang; Yongyi Chen; Li Qin; Lijun Wang (Micromachines)
Since surface relief transmission gratings have very strict requirements on operators and use environment, according to the semiconductor laser external cavity spectral beam combining system, this paper proposes a design scheme for a semiconductor laser array spectral beam combining system based on the grating-external cavity. The finite element approach was used to create a wideband, high-efficiency fill-in multilayer dielectric transmission grating structure for a high-power spectrum beam combining system. The incidence angle, ridge height, duty cycle, and sidewall inclination angle of the transmission grating were tuned and evaluated, and a link between the transmission grating’s diffraction efficiency and grating characteristics was discovered. The calculated design of the high-power fused silica transmission grating has a negative first-order peak diffraction efficiency of 99.5% in the 800 nm range. In the spectral region of 765–872 nm, the transmission grating’s diffraction effectiveness exceeds 92%. The filled ultra-high diffraction efficiency multilayer dielectric transmission grating design addresses the issue of resistance to high-power lasers under complicated operating settings. It is intended to maintain a high diffraction efficiency even after several cleaning cycles, and it is an ideal component for high-power spectrum beam combining systems.